Recreación Laboral Derecho Fundamental en la Relaciones de Trabajo. (Encuentros, 2024)
Workers are biopsychosocial beings, they require flexible work hours where family, personal and emotional development is taken into account so that it does not violate dignity and its potential; Thus, recreation and respect for the daily work to be done are strategies that make greater productivity possible, therefore, this scientific document addresses the elements, concepts and foundations of Work Recreation constitutional legal regulation, based on the methodology qualitative, documentary hermeneutic using bibliographic review, documentary analysis and observation, reaching conclusions that detail the normative compendium in permanent defense of Work relationships through the exercise of the Right to Recreation.
Keywords: Recreation, Labor Relations, Fundamental Law, work, everyday life